La rotación de personal en los centros de atención telefónica: una revisión de literatura (2021)
This document aims to carry out a literary review and research aimed at the análisis of the main causes of the Rotation of personnel that occurs in the telephone service centers. To carry out the development of this review and research was carried out through the systematic review approach for the collection of relevant information that has been carried out over time, this in order to address directly the causes of high staff turnover.